2020
DOI: 10.1111/jopr.13138
|View full text |Cite
|
Sign up to set email alerts
|

Intaglio Surface Dimension and Guide Tube Deviations of Implant Surgical Guides Influenced by Printing Layer Thickness and Angulation Setting

Abstract: Purpose:To measure overall intaglio dimensional and tube deviations of implant guides printed at 50 and 100 µm layer thickness at 0°, 45°, and 90°angulation using a stereolithographic (SLA) printer. Materials and Methods: A surgical implant guide design from a subject missing a maxillary right central incisor, used as the original standard tessellation language (STL) were stereolithographically fabricated at each thickness and angulation, 50 and 100 µm layer thickness at 0°, 45°, and 90°angulation (n = 10 each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 27 publications
4
58
1
Order By: Relevance
“…In addition, the difference between the guide design method of the pilot guide and the fully guide, the 3d printing method used, and the post-processing method may also influence the difference. Dalal et al reported that deviation of 0.04~0.26 mm and~2 • can be shown depending on the printing layer thickness and angulation setting value [18]. In this study, the guide of pilot-guided surgery was designed by the operator, and the guide of fully guided surgery was designed by the manufacturer and confirmed the planned data.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, the difference between the guide design method of the pilot guide and the fully guide, the 3d printing method used, and the post-processing method may also influence the difference. Dalal et al reported that deviation of 0.04~0.26 mm and~2 • can be shown depending on the printing layer thickness and angulation setting value [18]. In this study, the guide of pilot-guided surgery was designed by the operator, and the guide of fully guided surgery was designed by the manufacturer and confirmed the planned data.…”
Section: Discussionsupporting
confidence: 55%
“…The STL file of the guides from the Blue Sky Bio and 3D Slicer/Blender were printed, 10 guides for each group using Form 2 (Formlabs, Somerville, MA) SLA printer. Using printing parameters similar to previous reports, 1,3,4,18,19 the guides were oriented at ∼45°with appropriate generated supports. The guides were printed using Dental SG resin (Formlabs, Somerville, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty identical dental casts generated from the intraoral scan were printed using Dental Model resin (Formlabs, Somerville, MA). A similar post-processing method to previous studies, 1,3,4,18,19 was used, including rinsing twice with 96% isopropanol for 5 minutes each, then placing the guides/casts in ultrasonic with 96% isopropanol for additional 5 minutes. The guides and casts were allowed to air dry and then subjected to UV-A (315-400 nm) and UV-B (400-550) light in the polymerization chamber (LC-3D Print Box, NextDent, Soesterberg, The Netherlands) for 60 minutes at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…Then the guide was rinsed again with 96% isopropanol with a wash bottle for about 30 second (sec) and then placed in a plastic container with 96% isopropanol in the ultrasonic bath for an additional 5 minutes. This method was slightly modified from previous studies 3,8 . Then the guide was air‐dried using compressed air and then placed in a polymerization chamber (LC‐3D Print Box, NextDent) for 60 minutes subjected to UV‐A (315‐400 nm) and UV‐B (400‐550 nm) and heat (60°C).…”
Section: Methodsmentioning
confidence: 99%
“…Static implant guided surgery is currently the most accurate method to place an implant 4 . Recently introduction of in‐office stereolithographic printers allowed clinicians to produce implant surgical guides with lower cost, with the promise of higher accuracy than free‐hand or conventional implant guide methods 5‐9 …”
mentioning
confidence: 99%